Pauropods (Myriapoda: Pauropoda) from eastern China, descriptions of three new species and revision of Pauropus bifurcus Zhang & Chen, 1988 - Qian, Changyuan; Dong, Yan; Guo, Hua; Chu, Kelin; Sun, Hongying (Zootaxa, 2013)
Pauropods from Zhejiang and Jiangsu in eastern China were collected from the field. Among 23 specimens, four species assigned to two genera are identified. Three of these species are new and from the genus Decapauropus Remy, 1931: Decapauropus bifurcodicoccus Qian & Dong sp. nov., D. duomamillatus Qian & Dong sp. nov. and D. bidrepanoides Qian sp. nov. The status of Pauropus bifurcus Zhang & Chen, 1988 is reexamined and reallocated to the genus Stylopauropus Cook, 1896. A key to Decapauropus species of eastern China (including Jiangsu, Anhui and Zhejiang province) is provided.